Does the adoption of solid cooking fuel contribute to adverse child health outcomes? A Propensity Score Matched (PSM) analysis from Bangladesh Demographic and Health Survey, 2011- 2018 - Chowdhury, Rupok (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2022.